Distributional and revenue effects of a tax shift from labor to property - Jörg Paetzold; Markus Tiefenbacher (University of Essex, Institute for Social and Economic Research (ISER), 2016)
Contrary to frequent recommendations of the public finance literature and international institutions, a persistently high tax wedge on labor is observed in Europe. Simultaneously, the scope for shifting taxes to more growth-friendly revenue sources appears underused. This motivates our simulation of a tax shift from labor to property for Germany, a country where property tax revenues are particularly low and the tax wedge on labor income is among the highest in industrialized countries. We simulate a reform where property is no longer taxed by its (often) outdated cadastral value but by its market value, using the additional revenue to reduce social insurance contributions (SIC). To make such a simulation possible, we match property-related information with the input data of the tax-benefit microsimulation model EUROMOD. We find a considerable increase in property tax revenues, allowing to reduce the implicit tax rate on labor from 37.2% to 36.5%. Distributive effects tend to be modest, and depend critically on the design of the SIC reduction. Overall, our results suggest that more households would gain than lose from the tax shift, with gainers mostly situated in the middle of the income distribution.
Keywords: D31; C63; R20; H20; 330; labor taxes; property taxes; microsimulations; EUROMOD